Culture and Sustainability: Where Next? - Marcus, Marshall (Ökologisches Wirtschaften - Fachzeitschrift, 2022)
When we pose the question: “Who” has the power to help the world to act more sustainably, the obvious answer characteristically includes entities like governments, international organisations, NGOs, lobbyists, and the world of economics and commerce. But perhaps there is an additional answer that such a list misses: The field of culture and cultural practitioners.